Prediction of LEAP centrifuge test results using a pressure-dependent bounding surface constitutive model. Issue 113 (October 2018) - Ghofrani, Alborz; Arduino, Pedro
Abstract: In accordance with the "Liquefaction Experiments and Analysis Projects (LEAP )" guidelines, class-A, B and C predictions are performed for the response of centrifuge tests on a sloped configuration of Ottawa-F65 soil in a rigid container. The objective of this paper is to discuss important aspects on the calibration process of a pressure-dependent bounding surface constitutive model for the simulation of centrifuge experiments. The constitutive model used in this study is based on the theory of Critical State Soil Mechanics that has shown to be suitable to represent the behavior of cohesionless soils. Results of class-A predictions match experiment data reasonably well. An attempt is made to find a single set of material parameters to be used for class-B and class-C prediction of all six centrifuge tests. Abstract : Highlights: Details of a finite element model used for simulating centrifuge test are given. Results of class-A, B and C prediction on centrifuge tests are presented and discussed. Discussion on calibration of a constitutive model is given. Finding a single set of representative material parameter to be used in simulation of different centrifuge experiments is found to be impractical.